PELAKSANAAN MANAJEMEN BERBASIS MADRASAH DI MTS NEGERI 2 PADANG LAWAS UTARA - Salim, Salim; Ritonga, Zerni Mandasari Br.; Siahaan, Ahmad Taufik Al Afkari (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The purpose of this study was to determine (1) the efforts of the Head of Madrasah in Improving Madrasah-Based Management at MTs Negeri 2 Padang Lawas Utar in improving the quality of learning. (2) the form of monitoring and evaluation carried out by the head of madrasah in improving madrasah-based management at MTs Negeri 2 Padang Lawas Utara. The research method used is qualitative research. The approach used is descriptive qualitative. The data analysis used was the Miles and Huberman model through data reduction, data presentation, and conclusion / verification. To test the validity of the data, a credibility test was carried out using triangulation techniques, transferability tests, dependability tests and conformity tests. Based on the results of the discussion of the research data, the following conclusions were obtained: (1) the efforts of the head of madrasah in improving madarsah-based management at MTs Negeri 2 Padang Lawas Utara, namely: As an educator, manager, administrator, supervisor, leader, innovator, motivator. The leadership role of the head of madrasah in improving MBM: a) Describing the vision into a mission to achieve quality targets, b) The head of madrasah formulates the objectives and quality targets to be achieved, (c) Involves the teacher council and administration in making important madrasah decisions, f) Provide and increase work motivation. This aims to determine the extent to which things have been achieved from the predetermined plan. can come up with creative ideas and be able to encourage change for the better, the evaluation that is carried out does not only focus on teaching and learning activities, there are also some things that must be touched by the evaluation function, including human resources (educators and education staff), input (students), facilities, finance and relations with the community. This can and has a very important role in improving the image and quality of the institution. (3) Supporting factors for improving the MBM at MTs Negeri 2 Padang Lawas Utara. (a). MTs Negeri 2 Padang Lawas Utara is located on the main route of the village, so that access to education for teachers or students is quite good, (b). Have adequate facilities and infrastructure, starting from the field and quite large land ownership, (c). There is cohesiveness between teachers in supporting all policies made by the madrasah. 4) Inhibiting factors to increase the MBM in MTs Negeri 2 Padang Lawas Utara. Lack of funding, and human resources that are not in accordance with the wishes of the institution.